2015
DOI: 10.1002/jbm.b.33429
|View full text |Cite
|
Sign up to set email alerts
|

Development of a ubiquitously transferrable silver‐nanoparticle‐loaded polymer nanosheet as an antimicrobial coating

Abstract: Ultra-thin polymer films (nanosheets) fabricated by a layer-by-layer (LbL) method possess unique properties such as high flexibility, adhesive strength, and transparency, and can be peeled off from a substrate and attached to various surfaces via a water-soluble supporting film. Therefore, flexible and transferrable LbL nanosheets are convenient tools as coating materials. Here, we fabricated a novel antimicrobial coating material by embedding silver nanoparticles (AgNPs) in an LbL nanosheet composed of layers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Ito et al have prepared a highly flexible, strong adhesion, and transferrable AgNPs-loaded polymer nanosheet using the layer-by-layer assembly technique [ 43 ]. Here, poly (ethyleneimine) (PEI) is a cationic polymer and could adhere on SS/PVA film surface via the electric interaction between PEI and the negatively charged groups exposed on the surface of SS/PVA film.…”
Section: Resultsmentioning
confidence: 99%
“…Ito et al have prepared a highly flexible, strong adhesion, and transferrable AgNPs-loaded polymer nanosheet using the layer-by-layer assembly technique [ 43 ]. Here, poly (ethyleneimine) (PEI) is a cationic polymer and could adhere on SS/PVA film surface via the electric interaction between PEI and the negatively charged groups exposed on the surface of SS/PVA film.…”
Section: Resultsmentioning
confidence: 99%
“…The results suggest that ASC spheroids carried by the nanosheet can be used for treatment of skin/subcutaneous tissue resulting from various diseases such as critical limb ischemia. Additionally, our previous studies showed that medicinal ingredients (e.g., silver nanoparticles 41 and tetracycline 42 ) can be easily carried inside a nanosheet. By using this scheme, further enhancement of wound healing is expected.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also fabricated an antimicrobial NS by embedding silver nanoparticles. 7 However, the NS could not be peeled off and then repasted after adhesion to the organ surface which was a problem when the NS had been initially pasted at a slightly different location than intended. To paste such NSs in precise positions, Taccola and colleagues 8,9 developed the NSs with embedded magnetic nanoparticles and evaluated their morphology and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%